SHORT-TERM RESULTS OF MINIMALLY INVASIVE TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE BY RADIOFREQUENCY (STRETTA): FIRST BRAZILIAN SERIES OF CASES - SOUZA,Thiago Ferreira de (2018)
ABSTRACT BACKGROUND: New endoscopic treatments for gastroesophageal reflux (GERD) are developed every year and are indicated in cases that are refractory to conventional therapies as well as after surgical treatment failure. OBJECTIVE: To present the first cases of endoscopic therapy for GERD performed in Brazil. METHODS: Use of radiofrequency with the Stretta procedure in symptomatic volunteers diagnosed with GERD. RESULTS The technique was performed in three patients after they were included in the study protocol. No patient had complications, and all patients were discharged on the same day, either without medication or taking it sporadically for symptom control. CONCLUSION: Endoscopic treatment for GERD using radiofrequency was effective in the cases presented herein with no technical complications.